ساب معاملي التشوه ( لنظائر التنجستن الشفعية- شفعية (Comprehensive Journal of Science, 2026)
In this study the and  deformation parameters for the even-even  168-188W  isotopes have been calculated by the electric transition probability and the intrinsic electric quadrupole moment respectively. our results have good agreement with the y-rast experimental results. This research showed that the maximum values of the deformation parameters of the under study isotopes  were happened at  and near the mid-shell(N=104).
Keywords: Deformation parameters, electric transition probability Intrinsic, electric quadrupole moment, Tungsten Isotopes, even-even Isotopes